Noonans Syndrome of a 25 years old female - Haque, M Sirajul; Ahmed, Riaz Uddin; Rahman, Md Mahmudur (Bangladesh Journal of Medical Science, 2009)
Noonan's syndrome is an autosomal dominant disorder with a webbed neck that mimics turner syndrome. However, the syndrome has also been found to be genetically heterogeneous. Noonan syndrome is characterized by short stature, hyperkeratosis of skin, distinct facial features, lymphoreticular abnormalities, nail dystrophy. No abnormality in chromosome number has so far been reported. Here we present a 25 year old female who came to Bangladesh Medical College Hospital in May'08, with generalized skin eruptions and left leg swelling. Key words: Noonan's syndrome, genetic disorders DOI: 10.3329/bjms.v8i3.3986 Bangladesh Journal of Medical Sciences Vol.8(3) 2009 p68-71